Inequality in researchers’ minds: Four guiding questions for studying subjective perceptions of economic inequality - Jachimowicz, Jon M.; Davidai, Shai; Goya‐Tocchetto, Daniela; Szaszi, Barnabas; Day, Martin V.; Tepper, Stephanie J.; Phillips, L. Taylor; Mirza, M. Usman; Ordabayeva, Nailya; Hauser, Oliver P. (Journal of economic surveys, 2023)
Subjective perceptions of inequality can substantially influence policy attitudes, public health metrics, and societal well‐being, but the lack of consensus in the scientific community on how to best operationalize and measure these perceptions may impede progress on the topic. Here, we provide a theoretical framework for the study of subjective perceptions of inequality, which brings critical differences to light. This framework—which we conceptualize as a series of four guiding questions for studying subjective perceptions of economic inequality —serves as a blueprint for the theoretical and empirical decisions researchers need to address in the study of when , how , and why subjective perceptions of inequality are consequential for individuals, groups, and societies. To lay the foundation for a comprehensive approach to the topic, we offer four theoretical and empirical decisions in studying subjective perceptions of inequality, urging researchers to specify: (1) What kind of inequality? (2) What level of analysis? (3) What part of the distribution? and (4) What comparison group? We subsequently discuss how this framework can be used to organize existing research and highlight its utility in guiding future research across the social sciences in both the theory and measurement of subjective perceptions of inequality.